2011
DOI: 10.1210/en.2011-1406
|View full text |Cite
|
Sign up to set email alerts
|

The Multidrug Resistance-Associated Protein 4 (MRP4) Appears as a Functional Carrier of Prostaglandins Regulated by Oxytocin in the Bovine Endometrium

Abstract: Prostaglandins (PG) are involved in several female reproductive processes, and their action is regulated at the levels of biosynthesis, catabolism, and signal transduction. Facilitated transport across cell membranes emerges as an additional checkpoint regulating PG action. We have already reported on the influx transporter solute carrier organic anion transporting polypeptide (SLCO2A1) [PG transporter (PGT)] in relation to PG action in the bovine endometrium. In the present study, we report on the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 50 publications
1
21
1
Order By: Relevance
“…This is in contrast to a previous report, where polarised bovine epithelial cells treated with OT had predominantly basolateral accumulation of PGF, but not PGE (Asselin et al 1996). However, porcine endometrial epithelial cells and the bovine endometrial epithelial cell line, bEEL, reportedly have predominantly basolateral release of both PGE and PGF (Bowen et al 1996, Lacroix-Pepin et al 2011. Prostaglandins are charged anions that diffuse poorly across cell membranes, thus require facilitated transport by the prostaglandin transporter (PGT) and multidrug resistance-associated protein 4 (MRP4; Schuster 1998, Banu et al 2003, Tithof et al 2007, Lacroix-Pepin et al 2011.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to a previous report, where polarised bovine epithelial cells treated with OT had predominantly basolateral accumulation of PGF, but not PGE (Asselin et al 1996). However, porcine endometrial epithelial cells and the bovine endometrial epithelial cell line, bEEL, reportedly have predominantly basolateral release of both PGE and PGF (Bowen et al 1996, Lacroix-Pepin et al 2011. Prostaglandins are charged anions that diffuse poorly across cell membranes, thus require facilitated transport by the prostaglandin transporter (PGT) and multidrug resistance-associated protein 4 (MRP4; Schuster 1998, Banu et al 2003, Tithof et al 2007, Lacroix-Pepin et al 2011.…”
Section: Discussioncontrasting
confidence: 99%
“…However, porcine endometrial epithelial cells and the bovine endometrial epithelial cell line, bEEL, reportedly have predominantly basolateral release of both PGE and PGF (Bowen et al 1996, Lacroix-Pepin et al 2011. Prostaglandins are charged anions that diffuse poorly across cell membranes, thus require facilitated transport by the prostaglandin transporter (PGT) and multidrug resistance-associated protein 4 (MRP4; Schuster 1998, Banu et al 2003, Tithof et al 2007, Lacroix-Pepin et al 2011. In the bovine reproductive tract, PGT is predominantly, but not exclusively, localised to the basolateral membrane of endometrial epithelial cells, whereas stromal cells have diffuse membrane expression of PGT (Banu et al 2003), and MRP4 appears to be specifically involved in the basolateral release of PGF and PGE by bEEL cells (Lacroix-Pepin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy to reduce platelet aggregation is to inhibit platelet phosphodiesterases (PDEs). 1 PDEs catalyze the hydrolysis of 39,59-cAMP to inactive 59-AMP by cleaving the PDE bond. This antithrombotic approach elevates the intracellular platelet cyclic AMP (cAMP) and impairs platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that upregulation/overexpression of MRP4 in colorectal cancer tissues and cell lines is correlated to high extracellular level of PGE 2 , suggesting its capacity in transporting PGE 2 [18]. Indeed, MRP4 has been reported to transport PGE 2 in the bovine endometrium [19] and that MRP4 knockout mice showed reduced litter size [20]. Given the importance of ENaC-regulated COX-2/PGE 2 signaling in embryo implantation and the PGE 2 -transporting capacity of MRP4, we hypothesized that MRP4 might be involved in mediating the ENaCdependent signaling required for embryo implantation.…”
Section: Introductionmentioning
confidence: 99%